Kegiatan Partisipasi Siswa Dalam Proses Pemilihan Osis sebagai Cerminan Penerapan Demokrasi Siswa Sekolah Menengah - L, Maria Dominika Lomi; Saputri, Nabila Ayu; Rahmawati, Shelfia; Chairunissa, Farasifa; Haryanti, Dwi; Putri, Deliya Salsabila; Wijaya, Nabila Rahindah (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This study delves into the pivotal role of student council (OSIS) elections in nurturing democratic values among Generation Z students within Indonesian high schools. As Indonesia witnesses the surge of Generation Z, recognized as the largest demographic cohort, their engagement in both scholastic and civic activities, including voting in elections, becomes crucial. This demographic has the potential to significantly influence the trajectory of the nation's democratic governance. Utilizing qualitative research methods, predominantly interviews, this study explores the depth of students comprehension and application of democratic principles, particularly in the context of OSIS elections. Findings suggest a nuanced understanding among students, with many recognizing OSIS elections as tangible manifestations of democratic processes. However, their grasp of democracy beyond its political connotations remains limited, reflecting a need for more comprehensive educational initiatives. While students acknowledge the significance of OSIS elections in shaping school dynamics and personal growth, individual interest emerges as a determining factor in their level of participation. Nonetheless, students generally exhibit positive attitudes towards OSIS elections, recognizing them as valuable learning experiences. In conclusion, this study underscores the imperative of embedding practical democratic education within the school curriculum to cultivate informed and engaged citizens. Recommendations include the integration of robust democratic education modules and the facilitation of workshops and seminars to deepen students' understanding of democratic principles and practices.